An Empirical Analysis on the Underpricing of Initial Public Offerings (IPOs): A China-India Comparison - Zhou, Yanjun (2016)
Abstract Signaling theory, winner’s curse theory, principal-agent theory, underwriter reputation theory, ex-ante uncertainty theory, time interval theory and industry-specific theory will be tested in this dissertation. China and India are selected to be studied due to exist of high level of underpricng in both countries. A sample size of 186 in the Chinese stock markets and 1175 in the Indian stock markets during 2010 to 2016 excluded 2013 is used to explain IPOs underpricing, respectively. The result form OLS regression shows that oversubscription rate has significant influence in both countries. Offering price also be used to explain IPOs in China and interval has a significant influence in India. Industry theory and ex-ante uncertainty theory appear to have influence in both countries. Underwriter reputation has the lowest explanation power in China and India.